2023
DOI: 10.1039/d2lc01194h
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-based microfluidic device for on-chip counter-diffusive crystallization and in situ X-ray crystallography at room temperature

Abstract: Proteins are long chains of amino acid residues that perform a myriad of functions in living organisms, including enzymatic reactions, signalling, and maintaining structural integrity. Protein function is determined directly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The construct used for the CaMKIIβ hub structures presented here includes all C‐terminal residues, but the last 3 to 5 residues are only well resolved in 1 out of 11 unique chains between the two structures. We compared an additional 14‐mer CaMKIIβ hub structure deposited at higher resolution (2.6 Å, PDB code: http://firstglance.jmol.org/fg.htm?mol=7URY) (Saha et al, 2023), where the last three to five residues are resolved in five out of seven unique chains. We observe that these terminal residues fold back toward the central pocket of their own hub domain (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The construct used for the CaMKIIβ hub structures presented here includes all C‐terminal residues, but the last 3 to 5 residues are only well resolved in 1 out of 11 unique chains between the two structures. We compared an additional 14‐mer CaMKIIβ hub structure deposited at higher resolution (2.6 Å, PDB code: http://firstglance.jmol.org/fg.htm?mol=7URY) (Saha et al, 2023), where the last three to five residues are resolved in five out of seven unique chains. We observe that these terminal residues fold back toward the central pocket of their own hub domain (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study determined a structure of the CaMKIIα hub domain bound to an analog of γ‐hydroxybutyrate (5‐HDC) in this arginine pocket and showed that this compound bound specifically to CaMKIIα (Leurs et al, 2021). Other hub structures also trap molecules in this pocket, for example the other 14‐mer CaMKIIβ hub structure (PDB code: http://firstglance.jmol.org/fg.htm?mol=7URY) shows malic acid bound in the pocket (Saha et al, 2023). The specificity for 5‐HDC is striking, and rather remarkable, given the high sequence conservation between CaMKII variants.…”
Section: Discussionmentioning
confidence: 99%
“…17 Other hub structures also trap molecules in this pocket, for example the other 14mer CaMKIIβ hub structure (PDB code: 7URY) shows malic acid bound in the pocket. 20 The specificity for 5-HDC is striking, and rather remarkable given the high sequence conservation between CaMKII variants. A major difference between the hub domains is that in CaMKIIα there are three arginines in the pocket, while in CaMKIIβ there are only two, and the third is substituted with cysteine (Figure S1b, c).…”
Section: Discussionmentioning
confidence: 99%
“…The construct used for the CaMKIIβ hub structures presented here includes all C-terminal residues, but the last 3-5 residues are only well-resolved in 1 out of 11 unique chains between the two structures. We compared an additional 14mer CaMKIIβ hub structure deposited at higher resolution (2.6 Å, PDB code: 7URY) 20 , where the last 3-5 residues are resolved in 5 out of 7 unique chains. We observe that these terminal residues fold back toward the central pocket of their own hub domain (Figure S1a).…”
Section: Two Camkiiβ Hub Stoichiometries From a Single Crystallizatio...mentioning
confidence: 99%
“…One of the main critical factors for applications in structural crystallography is the need for high-throughput screening to search for the optimal crystallization conditions for sample preparation, together with sample handling and manipulation for cryoprotection. On this matter, several microfluidic approaches have been proposed in the literature to tackle this issue, some of them proposed based on data collection at room temperature [ 164 , 165 , 166 , 167 , 168 , 169 ]. However, the ease of sample preparation–manipulation offered for these devices usually comes at the expense of increased background noise originating from the scattering of chip-fabrication materials, hence limiting the attainable resolution of the diffraction data.…”
Section: Scattering-based Detection Techniquesmentioning
confidence: 99%